Sustainability Report Disclosure Reviewed with Good Corporate Governance Mechanism - Pangestu, Ilham Ferdinan; Zulfikar, Z (Universitas Muhammadiyah Surakarta, 2024)
Objective: The objective of this study is to study how good corporate management mechanisms affect sustainability report disclosure. Methodology: This study uses quantitative methods and uses non-probability (purposive) examination techniques. A total of 81 samples that meet the criteria of companies listed in the LQ-45 Index are the subjects of this study. SPS software is used to analyze information through statistical analysis. Results: This study found that factors between the Board of Commissioners and the Board of Directors have a significant influence on the disclosure of sustainability reports. The results of the study indicate that a good partnership between the Board of Commissioners (operational supervisor) and the Board of Directors (operational person) can enable companies to report sustainability report disclosures widely. The combination of proper supervision and proper policy setting encourages companies to be proactive in. Application/Originality/Value: This study extends the stakeholder theory which states that the Board of Commissioners and the Board of Directors have a good relationship with sustainability disclosure. The GRI 2021 Index, which is the latest index, is used in this study.